Rain-Grove a stand-alone rainwater harvesting system designed for Ninoy Aquino Parks and Wildlife, Quezon City - Velarde, Gillian Pamela V.; Constantino, Nina Elisa B. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2016)
The interconnected systems of parks and green spaces that conserves natural ecosystem values and sustains clear air and water are a community necessity. According to the Environmental Science for Social Change, by this year the Philippines will experience drought with or without El Niño. The demand for water will escalate to a point that water allocation to parks will most likely be reduced in order to give way to households in need. Rain water is a vastly underused resource that we often take for granted. Rain water harvesting is an old-age concept that is increasing popularity today. With this, I designed a stand-alone rain water harvesting system for Ninoy Aquino Parks and Wildlife Center. Aside from it being a water utility system, it is also designed to function as a park attraction. This is also a perfect practice to responsible water management. Climate change is real.
Thesis (Bachelor of Fine Arts in Industrial Design)--University of the Philippines Diliman
Includes bibliography.
Keywords: Rainwater; Water harvesting